Pengaruh Terapi Musik Terhadap Penurunan Kecemasan Pasien Pre Kateterisasi Jantung (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of music therapy on reducing anxiety in pre-cardiac catheterization patients. The method used is quantitative with a quasi-experimental design. The data collection technique uses an anxiety questionnaire, namely HARS (Hamilton Rating Scale). The data analysis technique uses paired sample t-test. The results of the study showed that there was an effect of music therapy on reducing anxiety in pre-cardiac catheterization patients (p